Organic Molecular Paleohypsometry: A New Approach to Quantifying Paleotopography and Paleorelief - Hren, Michael T.; Ouimet, William (Frontiers in Earth Science, 2021)
Stable isotope paleoaltimetry is one of the most commonly used approaches for quantifying the paleoelevation history of an orogen yet this methodology is commonly limited to arid to semi-arid climates, mountain systems with a clear orographic rainshadow and terrestrial basins. We discusspresent a new approach to reconstructing past topography and relief and relief that uses the catchment-integrated signature of organic molecular biomarkers to quantify the hypsometry of fluvially-exported biomass. Because terrestrially-produced biomolecules are synthesized over the full range of global climate conditions and can be preserved in both terrestrial and marine sediments, the geochemistry of fluvially-transported sedimentary biomarkers can provide a means of interrogating the evolution of topography for a range of environments and depositional settings, including those not well suited for a traditional isotope paleoaltimetry approach. We show an example from Taiwan, a rapidly eroding tropical mountain system that is characterized by high rates of biomass production and short organic residence time and discuss key factors that can influence molecular isotope signal production, transport and integration. Data show that in high relief catchments of Taiwan, river sediments can record integration of biomass produced throughout the catchment. Sedimentary biomarker δ2HnC29 in low elevation river deposition sites is generally offset from the δ2HnC29 value observed in upland, local soils and consistent with an isotopic composition of organics produced at the catchment mean elevation. We test the effect of distinct molecular production and erosion functions on the expected δ2HnC29 in river sediments and show that elevation-dependent differences in the production and erosion of biomarkers/sediment may yield only modest differences in the catchment-integrated isotopic signal. Relating fluvial biomarker isotope records to quantitative estimates of paleotopography in other global orogens will likely pose numerous challenges, with a number of variables that influence molecular production and integration in a river system. We provide a discussion of important parameters that influence molecular biomarker isotope signatures in a mountain system and a framework for employing a molecular paleohypsometry approach to quantifying the evolution of other orogenic systems.